A Force Based Determination of Hot Cracking Susceptibility - Liepold, Philipp; Kromm, Arne; Kannengiesser, Thomas (Journal of Welding and Joining, 2025)
Two high-strength, low-alloy Gas Metal Arc Welding (GMAW) wires were evaluated for their susceptibility to Solidification Cracking (SC) using a modified version of the Transverse Motion Weldability (TMW) test1). In the original TMW test, the Transverse Displacement Speed (TDS) is varied iteratively, and crack lengths are measured in each iteration. The modified version eliminates the need for multiple runs by continuously reducing the TDS over a single run. Rather than emphasizing crack lengths, this method assesses the reaction force to the TDS, thereby determining a Critical TDS (CTDS). This critical point directly correlates with the cessation of SC growth.CTDS values were measured under a range of welding parameters, thereby demonstrating the influence of welding speed and arc energy (U × I/welding speed) on SC susceptibility for the tested filler metals. The CTDS data obtained from this testing method have the potential to provide valuable insights for practical applications in the field.